2008
DOI: 10.1016/j.jasms.2008.02.008
|View full text |Cite
|
Sign up to set email alerts
|

A novel serine phosphorylation site detected in the n-terminal domain of estrogen receptor isolated from human breast cancer cells

Abstract: Activated estrogen receptor (ER␣) plays a critical role in breast cancer development and is a major target for drug treatment. Serine phosphorylation within the N-terminal domain (NTD) contributes to ER␣ activation and may also cause drug resistance. Previous biochemical identification of phosphorylated ER␣ residues was limited to protein artificially overexpressed in transfected cell lines. We report mass spectrometric methods that have allowed the identification of a new site within the NTD of ER␣ isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…More recently we enriched and immunoaffinity-purified endogenous ER␣ derived from the human breast cancer cell line MCF-7 in quantities compatible with tandem MS analysis and identified a novel phosphorylation site, Ser 154 . vMALDI-MS n confirmed Ser 154 phosphorylation in human breast cancer cells grown under both ligand-dependent and ligand-independent conditions (27). Coincidentally we also observed known phosphorylation sites Ser 118 and Ser 167 not previously confirmed by MS methods.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…More recently we enriched and immunoaffinity-purified endogenous ER␣ derived from the human breast cancer cell line MCF-7 in quantities compatible with tandem MS analysis and identified a novel phosphorylation site, Ser 154 . vMALDI-MS n confirmed Ser 154 phosphorylation in human breast cancer cells grown under both ligand-dependent and ligand-independent conditions (27). Coincidentally we also observed known phosphorylation sites Ser 118 and Ser 167 not previously confirmed by MS methods.…”
supporting
confidence: 76%
“…Reagents and Chemicals-These were as described previously (27) except that human recombinant ER␣ (rER␣) was from Invitrogen, and sequencing grade chymotrypsin, Lys-C, Asp-N, and Glu-C were from Roche Diagnostics.…”
Section: Methodsmentioning
confidence: 99%
“…1 et al 1995b). Recently, novel phosphorylation sites in ERa were identified (Britton et al 2008. Table 1 lists the sites of phosphorylation in ERa, which have been identified experimentally, using different methodologies.…”
Section: Phosphorylation Sites Identified In Eramentioning
confidence: 99%
“…The presence of multiple phosphorylation sites in ERa (Britton et al 2008, Murphy et al 2009a) that may have differential effects on activity suggests that it may be necessary to consider the balance of multiple phosphorylation sites in vivo in terms of predicting clinical outcome with respect to endocrine treatment responsiveness. Recently, data have been published where up to seven different phosphorylation sites in ERa in any individual tumor were taken into account by developing a mathematical model that balances the presence of phosphorylation sites associated with good clinical benefit and those associated with poor clinical benefit.…”
Section: Multiple Phosphorylated Forms Of Eramentioning
confidence: 99%
“…This EGF-induced ER escape from hormone regulation could be explained by evidence that EGF triggers ligand-independent ER transcriptional activity through phosphorylation of specific critical residue(s) of nuclear estrogen receptor promoting interaction with its co-activator SRC1 (Schiff et al, 2003). EGF stimulates through MAPK-dependent signaling ERalpha serine phosphorylation on 118 (Kato et al, 1995) and 154 residues (Britton et al, 2008), likely enhances 305 serine phosphorylation (Rayala et al, 2006), and induces 167 serine phosphorylation through a PI3-K dependent pathway (Campbell et al, 2001). It has also been shown that EGF activated MAPK pathway can phosphorylate the ER coactivator AIB1 and nuclear co-repressor NCoR (Font de Mora & Brown, 2000).…”
mentioning
confidence: 99%